Studies on Creep Deformation and Rupture Behavior of 316LN SS Multi-Pass Weld Joints Fabricated with Two Different Electrode Sizes - Vijayanand, V. D.; Kumar, J. Ganesh; Parida, P. K.; Ganesan, V.; Laha, K. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2017)
Effect of electrode size on creep deformation and rupture behavior has been assessed by carrying out creep tests at 923 K (650 °C) over the stress range 140 to 225 MPa on 316LN stainless steel weld joints fabricated employing 2.5 and 4 mm diameter electrodes. The multi-pass welding technique not only changes the morphology of delta ferrite from vermicular to globular in the previous weld bead region near to the weld bead interface, but also subjects the region to thermo-mechanical heat treatment to generate appreciable strength gradient. Electron backscatter diffraction analysis revealed significant localized strain gradients in regions adjoining the weld pass interface for the joint fabricated with large electrode size. Larger electrode diameter joint exhibited higher creep rupture strength than the smaller diameter electrode joint. However, both the joints had lower creep rupture strength than the base metal. Failure in the joints was associated with microstructural instability in the fusion zone, and the vermicular delta ferrite zone was more prone to creep cavitation. Larger electrode diameter joint was found to be more resistant to failure caused by creep cavitation than the smaller diameter electrode joint. This has been attributed to the larger strength gradient between the beads and significant separation between the cavity prone vermicular delta ferrite zones which hindered the cavity growth. Close proximity of cavitated zones in smaller electrode joint facilitated their faster coalescence leading to more reduction in creep rupture strength. Failure location in the joints was found to depend on the electrode size and applied stress. The change in failure location has been assessed on performing finite element analysis of stress distribution across the joint on incorporating tensile and creep strengths of different constituents of joints, estimated by ball indentation and impression creep testing techniques.